Experimental Study on Solar Drying of Arabica Coffee Beans: Achieving Standard Moisture Content Using a Drying Chamber Collector - Hilman Mafazi; Selly Septianissa; Ahmad Rajani (Logic : Jurnal Rancang Bangun dan Teknologi, 2025)
Drying technology plays a critical role in preserving and enhancing the quality of agricultural products, particularly in the post-harvest handling of Arabica coffee. In this experimental study, Arabica coffee beans were dried using a solar drying chamber equipped with a collector system to achieve standard moisture content. A total of 6000 grams of coffee beans were dried over 28 hours, with the system operating under an average chamber temperature of 40°C and a peak solar radiation intensity of 1122 W/m² occurring at 12:00 PM. The drying process utilized an air velocity of 9.2 m/s to enhance heat and mass transfer within the chamber. Among all trays tested, tray 2 produced the best quality beans with a final moisture content of 11.8%, aligning with the recommended standard for green coffee storage. These results demonstrate that integrating high air velocity and optimized collector design in a solar drying chamber can significantly reduce moisture content while maintaining bean quality, thereby offering an effective and sustainable alternative to conventional drying methods.